Handbook of transport and the environment - Hensher, David A., 1947-; Button, Kenneth, 1948- (Handbooks in transport, 2003)
As one of the most challenging issues facing the transport sector, the need for this handbook devoted to the environmental impacts of transport is clear. It gives full treatment to all aspects of the subject such as: environmental concepts, both physical and economic - key environmental concerns: global warming, air quality, noise, safety, amenity, and severance; the role of fuel sources and new technology in reducing environmental externalities; the contribution of each transport sector to energy consumption and emissions - appraisal, valuation, and impacts of externalities; institutional and political settings and policies - the role of environmental legislation; and special topics such as tourism, public attitudes, and gender. Each chapter was specially commissioned from an acknowledged world expert on the topic. Each offers an overview and useful insights to those familiar with the area as well as those new to it. Systematic and thorough in its creation, current and acessible in its content, and authoritative and international in its authorship, the "Handbook of Transport and the Environment" will be the definitive reference work on this important subject.